MELATONIN: ANYTHING MORE THAN CIRCANIAN CYCLE? PHYSIOLOGIC, PATOPHYSILOGIC AND TERAPEUTIC ASPECTS. - Léon Páez, Pamela (2019)
Melatonin is a hormone synthetized mainly by the pineal gland. Its secretion has a defined circadian rhythm and it presents high serum values during the day but almost undetectable at night. This circadian rhythm in humans depends on postranslational regulation as ubiquitination and aralkylamine N-acetyltransferase´s proteolysis. For several years this gland was considered the only endogenous source of melatonin. Nowadays it is well known that melatonin is produced by the retina, gastrointestinal tract, skin, platelets, bone marrow, liver and other cells. There are two types of melatonin receptors, which are distributed in multiple organs. The role of melatonin as a regulator of gastrointestinal transit and as a contributor to the status of euglycemia has been described. It also acts as an antioxidant agent, in the context of acute myocardial infarction and hypoxic ischemic encephalopathy. Currently there are several melatonergic agonists with specific indications. At this time there are multiple clinical trials that seek to expand the therapeutic horizons of melatonin.